1998
DOI: 10.1111/j.1574-6968.1998.tb13190.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic requirements for the expression of benzylamine dehydrogenase activity in Pseudomonas putida

Abstract: Pseudomonas putida grows on benzylamine as a sole source of carbon/energy and nitrogen. Synthesis of an inducible benzylamine dehydrogenase (BMDH) depends on the specific RNA polymerase sigma factor σ54 and is subject to carbon source‐dependent inhibition. The presence of TOL plasmid pWW0 harboring the genetic information for the catabolism of toluene exerts strong inhibition of induction of BMDH activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Catabolite repression has been reported in a number of Pseudomonas strains for a variety of aromatic carbon assimilation routes including toluene [42], phenol [43], benzylamine [44], chloroaromatics [45] and ethylbenzene [46]. Similarly, it has been reported that a number of non-aromatic carbon sources such as organic acids and/or carbohydrates repress styrene degradation in both P. putida CA-3 and P. £uorescens ST [9,19,34].…”
Section: Catabolite Repressionmentioning
confidence: 91%
“…Catabolite repression has been reported in a number of Pseudomonas strains for a variety of aromatic carbon assimilation routes including toluene [42], phenol [43], benzylamine [44], chloroaromatics [45] and ethylbenzene [46]. Similarly, it has been reported that a number of non-aromatic carbon sources such as organic acids and/or carbohydrates repress styrene degradation in both P. putida CA-3 and P. £uorescens ST [9,19,34].…”
Section: Catabolite Repressionmentioning
confidence: 91%